PRNP expression predicts imaging findings in sporadic Creutzfeldt‐Jakob disease. Issue 4 (6th February 2023) - Broce, Iris J.; Caverzasi, Eduardo; Sacco, Simone; Nillo, Ryan Michael; Paoletti, Matteo; Desikan, Rahul S.; Geschwind, Michael; Sugrue, Leo P.
Abstract: Objective: We explored the relationship between regional PRNP expression from healthy brain tissue and patterns of increased and decreased diffusion and regional brain atrophy in patients with sporadic Creutzfeldt‐Jakob disease (sCJD). Methods: We used PRNP microarray data from 6 healthy adult brains from Allen Brain Institute and T1‐weighted and diffusion‐weighted MRIs from 34 patients diagnosed with sCJD and 30 age‐ and sex‐matched healthy controls to construct partial correlation matrices across brain regions for specific measures of interest: PRNP expression, mean diffusivity, volume, cortical thickness, and local gyrification index, a measure of cortical folding. Results: Regional patterns of PRNP expression in the healthy brain correlated with regional patterns of diffusion signal abnormalities and atrophy in sCJD. Among different measures of cortical morphology, regional patterns of local gyrification index in sCJD most strongly correlated with regional patterns of PRNP expression. At the vertex‐wise level, different molecular subtypes of sCJD showed distinct regional correlations in local gyrification index across the cortex. Local gyrification index correlation patterns most closely matched patterns of PRNP expression in sCJD subtypes known to have greatest pathologic involvement of the cerebral cortex. Interpretation: These results suggest that the specific genetic and molecular environment in which the prion protein is expressed confer variable vulnerability to misfolding across different brain regions that is reflected in patterns of imaging findings in sCJD. Further work in larger samples will be needed to determine whether these regional imaging patterns can serve as reliable markers of distinct disease subtypes to improve diagnosis and treatment targeting.